ANALYSIS AND EXPRESSION OF AL-TOLERANT GENES FROM SOYBEAN [Glycine max (L.) Merryl] ON FORAGE CROPS AND Escherichia coli - S. Anwar; Sumarsono Sumarsono; F. Kusmiyati (Udayana University)
n order to analyze and to study expressions of the Al-tolerant genes, we have examined five clone genes that were isolated from soybean cv. Lumut. Soybean cv. Lumut and Slamet, Centrocema pubescens, Pennisetum purpureum and Escherichia coli were selected for futher analysis. Based on the DNA sequencing, searching enzyme restriction sites and searching DNA homology with the genebank database; the clones encoding: (1) Catalase (gmali12, that function as an antioxidant), (2) Proliferating cell nuclear antigen like protein/PCNALP (gmali15, that involved as one of transcriptional regulator in the eucaryotic cell cycle), (3) Growth hormone (gmali22, this gene may play a role on stimulation of cell growth/development), (4) Amine oxidase (gmAO, genebank accession number AF313622, a gene that function as amine oxidation and/or antioxidant), and (5) Aminoacyl peptidase (gmAP, genebank accession number AF091304, a serine protease gene). Expressions of the clone genes either on forage crops or Escherichia coli indicated that all of the clones are basic genes, but its expression increased with aluminium induction (Al-induced genes) and involved in detoxification to Al stress. From this research, we also found similar responses between oxidative stress and Al stress to gene responses.